2011
DOI: 10.1007/s00005-011-0131-4
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NF-κB and HIF-1 Pathways for the Treatment of Cancer: Part I

Abstract: The process of chronic inflammation is a common link which connects different kinds of environmental pollutants and infections with tumorigenesis. Transcription factor NF-κB is a common final target for many inflammatory and cell proliferation pathways, independent of the source of stimuli (e.g., cytokines, growth factors, environmental carcinogens, radiation, hypoxia, bacteria, and viruses). Over-activation of NF-κB has been confirmed in many tumors, resulting in worse prognosis for patient survival. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 120 publications
0
24
0
Order By: Relevance
“…6 HIF-1 α can induce the expression of multiple target genes such as VEGF 29 (an important angiogenesis factor), CXCR4 30 (an important factor regulating cell migration), adenovirus E1B 19-kDa-interacting protein 3 (BNIP3) 31 (a pro-cell death member of the Bcl-2 family) and CAIX 31 (a marker for hypoxia). Thus, HIF-1 α can activate downstream pathways involved in proliferation, metabolism, differentiation and angiogenesis, 32, 33 which likely account for the ability of HIF-1 α to keep leukemic blasts at undifferentiated stages and therefore maintain a larger number of LSCs in the bone marrow. 34 It has been shown that silencing HIF-1 α in Jurkat cells significantly decreased their migration and infiltration capacity.…”
Section: Discussionmentioning
confidence: 99%
“…6 HIF-1 α can induce the expression of multiple target genes such as VEGF 29 (an important angiogenesis factor), CXCR4 30 (an important factor regulating cell migration), adenovirus E1B 19-kDa-interacting protein 3 (BNIP3) 31 (a pro-cell death member of the Bcl-2 family) and CAIX 31 (a marker for hypoxia). Thus, HIF-1 α can activate downstream pathways involved in proliferation, metabolism, differentiation and angiogenesis, 32, 33 which likely account for the ability of HIF-1 α to keep leukemic blasts at undifferentiated stages and therefore maintain a larger number of LSCs in the bone marrow. 34 It has been shown that silencing HIF-1 α in Jurkat cells significantly decreased their migration and infiltration capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Again, many natural products mostly with anti-inflammatory properties are NFkB inhibitors (Gupta et al, 2010). More than 700 inhibitors of NFkB have been identified so far and their importance is due to the central role that this transcription factor has for many pathologies, beside inflammation and cancer (Wilczynski et al, 2011). Some representative compounds acting at different steps of NFkB pathway are reported on Figure 5.…”
Section: Modulators Of Nfkb and Nfkb-dependent Genesmentioning
confidence: 99%
“…In particular, parthenolide seems to have an anti-tumoral activity also on cancer stem cells (Gunn et al, 2011). Anti-inflammatory drugs are IKK inhibitors although with an unknown mechanisms (Wilczynski et al, 2011). Among these there are: aspirin, ibuprofen, sulindac, sulfasalazine, and other NSAIDs (Kast, 2006).…”
Section: Modulators Of Nfkb and Nfkb-dependent Genesmentioning
confidence: 99%
“…1,2 Limited evidence of efficacy in clinical trials exists, although some TF antagonists (STAT3, -κB) are progressing through phase 1-2 trials. 3,4 …”
Section: Introductionmentioning
confidence: 99%